Common mental disorders through the eyes of German employees: attributed relevance of work-related causes and prevention measures assessed by a standardised survey - Burgess, Stephanie (Int Arch Occup Environ Health, 2019)
PURPOSE: Common mental disorders (CMDs) are becoming increasingly relevant in the working world. Numbers of risk factors have been confirmed by mostly correlative cross-sectional studies. Comprehensive and effective prevention is urgently needed. There is little knowledge about employees’ own perceptions on causes of CMDs and prevention measures. Therefore, a survey was conducted in 2016. METHODS: A standardised instrument was developed for an online survey in a commercial access panel, targeted employees in different job types. We assessed two outcomes: perceived relevance of (1) work-related demands to the development of CMDs, and (2) prevention approaches in the workplace and on individual and societal levels. Possible predictive aspects were analysed exploratively by multivariate linear regression analysis. RESULTS: The response rate was 75% (n = 610). Job types were categorised as “blue”, “grey” and “white-collar” workers (n = 193, 169, 248). The majority of respondents rated both outcomes consistently as “quite” or “very relevant”; societal prevention strategies were more relevant for non-white-collar workers. Perceived relevance of individual predisposition to develop a CMD was the strongest predictor for both outcomes, indicating the perception that people with higher personal vulnerability might suffer a higher strain from work-related risk factors than others. CONCLUSION: We assume that participants in our survey judged the relevance of work-related causes of CMDs independently of their own workload. The perceived relevance of prevention measures in different areas is consistent with official guidelines. A possible selection bias due to characteristics of access panel collectives and own direct or indirect experiences with CMD should be critically questioned. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00420-019-01414-7) contains supplementary material, which is available to authorized users.